2015
DOI: 10.1002/eco.1617
|View full text |Cite
|
Sign up to set email alerts
|

A rapid method to collect methane from peatland streams for radiocarbon analysis

Abstract: Peatland streams typically contain high methane concentrations and act as conduits for the release of this greenhouse gas to the atmosphere. Radiocarbon analysis provides a unique tracer that can be used to identify the methane source, and quantify the time elapsed between carbon fixation and return to the atmosphere as CH 4 . Few studies -those that have focus largely on sites with bubble (ebullition) emissions -have investigated the 14 C age of methane in surface waters because of the difficulty in collectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 42 publications
(70 reference statements)
0
20
0
Order By: Relevance
“…Direct in situ measurements of 14 CO 2 and 14 CH 4 signatures are needed to improve our understanding of the contribution of old C to inland water C emissions across a range of environmental settings. Methodological advances now allow for the collection of 14 CO 2 and 14 CH 4 samples relatively quickly and easily in even remote field locations (Billett et al, ; Dean et al, ; Garnett, Billett, et al, ; Garnett, Gulliver, et al, ). For aquatic CO 2 and CH 4 14 C samples, age distribution analysis (e.g., Dean, van der Velde, et al, ) or multisource isotopic mass balance (e.g., Elder et al, ) can help determine relative contributions of different aged C.…”
Section: Discussionmentioning
confidence: 99%
“…Direct in situ measurements of 14 CO 2 and 14 CH 4 signatures are needed to improve our understanding of the contribution of old C to inland water C emissions across a range of environmental settings. Methodological advances now allow for the collection of 14 CO 2 and 14 CH 4 samples relatively quickly and easily in even remote field locations (Billett et al, ; Dean et al, ; Garnett, Billett, et al, ; Garnett, Gulliver, et al, ). For aquatic CO 2 and CH 4 14 C samples, age distribution analysis (e.g., Dean, van der Velde, et al, ) or multisource isotopic mass balance (e.g., Elder et al, ) can help determine relative contributions of different aged C.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these field results suggesting that the samples were fully equilibrated within 2 min, we chose to standardize our sampling method with a shaking time of 3 min to allow for manual differences in shaking technique between operators. This was also consistent with our headspace equilibration method for the collection of methane samples for 14 C analysis (Garnett et al ., ), thus permitting the collection of samples of both CO 2 and CH 4 for 14 C analysis using the same equilibrated water sample.…”
Section: Discussionmentioning
confidence: 99%
“…Errors could arise because of either (1) a small contribution of geological carbonate contributing to gas‐stripped samples, and not the headspace‐equilibrated samples [for practical reasons, the water samples were not filtered, but a small particle of as little as ~2 mg 14 C‐dead CaCO 3 in the 485‐ml water sample would be sufficient to account for the discrepancy between headspace‐equilibrated and gas‐stripped results; although the stream flows from a peatland, the underlying geological formation (Clackmannan Group) does contain limestone; British Geological Society; http://mapapps.bgs.ac.uk/geologyofbritain/home.html]; (2) disequilibrium between aquatic CO 2 and DIC due to unfavourable mixing in the stream (suggested by Billett and Garnett, , who also reported older ages for gas‐stripped DIC samples compared with CO 2 collected using a floating chamber); and (3) a sample preservation issue (the DIC sample was stored for ~4 months in a refrigerator without any other means of sample preservation, prior to processing, and therefore, transfer of carbon between different inorganic pools within the sample may have occurred. Although we did not measure methane during this study, it has previously been found to be abundant and much older than CO 2 at this site (up to 3291 years BP; Garnett et al ., ), and so methane oxidation during sample storage could explain a significant proportion of the offset between headspace‐equilibrated and gas‐stripped samples). In this respect, it should be noted that by avoiding the need for the acidification of water samples, and instead relying on rapid equilibration of samples by shaking and the isolation of aquatic CO 2 from the water sample in the field and stable storage on molecular sieve, the new method completely avoids all of the confounding issues associated with the gas‐stripping method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations